Biological ice nucleation initiates hailstone formation. Issue 21 (6th November 2014) - Michaud, Alexander B.; Dore, John E.; Leslie, Deborah; Lyons, W. Berry; Sands, David C.; Priscu, John C.
Abstract: Cloud condensation and ice nuclei in the troposphere are required precursors to cloud and precipitation formation, both of which influence the radiative balance of Earth. The initial stage of hailstone formation (i.e., the embryo) and the subsequent layered growth allow hail to be used as a model for the study of nucleation processes in precipitation. By virtue of the preserved particle and isotopic record captured by hailstones, they represent a unique form of precipitation that allows direct characterization of the particles present during atmospheric ice nucleation. Despite the ecological and economic consequences of hail storms, the dynamics of hailstone nucleation, and thus their formation, are not well understood. Our experiments show that hailstone embryos from three Rocky Mountain storms contained biological ice nuclei capable of freezing water at warm, subzero (°C) temperatures, indicating that biological particles can act as nucleation sites for hailstone formation. These results are corroborated by analysis of δD and δ 18 O from melted hailstone embryos, which show that the hailstones formed at similarly warm temperatures in situ. Low densities of ice nucleation active abiotic particles were also present in hailstone embryos, but their low concentration indicates they were not likely to have catalyzed ice formation at the warm temperatures determined from water stable isotope analysis. Our study provides new data on ice nucleation occurring at the bottom of clouds, an atmospheric region whose processes are critical to global climate models but which has challenged instrument‐based measurements. Key Points: Active biological ice nuclei are present in the embryos of hailstones Water stable isotopes reveal warm, subzero freezing of hailstone embryos Layered hailstone growth allows direct study of ice nucleation